ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MEMECAHKAN MASALAH DIVERGEN SUB POKOK BAHASAN SEGITIGA DAN SEGIEMPAT BERDASARKAN KEMAMPUAN MATEMATIKA - Sugiarti, Titik; Sunardi, Sunardi; Desbi, Alina Mahdia (Department of Mathematics Education , University of Jember, 2016)
Abstract. Creative thinking ability is the ability to generate ideas or new ways to produce a product Creative thinking ability can be raised by giving the problems that have more than one solution in various ways or also called divergent problems. This research aimed to describe the student’s creative thinking ability in solving the divergent problems of triangular and quadrilateral subjects based on mathematical ability. The type of this research is descriptive qualitative research with the subject of students class VIII SMPN 1 Jember amounted to 10 students who have categorized the ability of mathematics. Methods of data collection in this research are documentation, tests and interviews. Based on the results of the test of creative thinking ability and interview, the ability of high mathematics students belong to the third level that is creative, the ability of mathematics students are classified at several levels, namely level 1 (less creative), level 2 (creative enough), and level 4 (very creative) , And the ability of low mathematics students also belong to several levels, namely level 2 (creative enough), level 3 (creative), and level 4 (very creative). The ability of students' creative thinking in solving divergent problems based on the ability of mathematics is varied and does not depend on the category of mathematical ability possessed. Keywords: Creative Thinking Ability, Divergent Problem, Mathematical Ability